The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1097/01.mib.0000171277.70404.40
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Mesalamine 1 g HS Versus 500 mg BID Suppositories in Mild to Moderate Ulcerative Proctitis: A Multicenter Randomized Study

Abstract: This study showed that 1 g HS and 500 mg BID mesalamine suppository treatments of UP patients were equivalent in all facets of efficacy, safety, and compliance in a 6-week trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 7 publications
3
38
0
Order By: Relevance
“…23 A recent study has demonstrated that once-aday 5-ASA suppository has comparable efficacy (disease activity index), safety, and compliance (.95% in both groups) to a twicedaily 5-ASA suppositories in patients with ulcerative proctitis. 24 The patient-level interviews in this study provide insights into the barriers to adherence to rectal formulations as recommended in the development of patient-reported outcomes. 25 From our analyses, we found that issues with administration and intentional nonadherence were common themes in these interviews.…”
Section: Discussionmentioning
confidence: 99%
“…23 A recent study has demonstrated that once-aday 5-ASA suppository has comparable efficacy (disease activity index), safety, and compliance (.95% in both groups) to a twicedaily 5-ASA suppositories in patients with ulcerative proctitis. 24 The patient-level interviews in this study provide insights into the barriers to adherence to rectal formulations as recommended in the development of patient-reported outcomes. 25 From our analyses, we found that issues with administration and intentional nonadherence were common themes in these interviews.…”
Section: Discussionmentioning
confidence: 99%
“…Novel delivery systems and higher dosing formulations of 5-ASA are also in development. These include the once-daily oral multimatrix (MMx) 5-ASA (SPD476) formulation [34,35] ; a twice-daily oral micropellet formulation [36] ; a once-daily, slow-release suppository formulation [37] ; and a 5-ASA rectal gel that treats the left colon and in early trials is preferred by patients over existing 5-ASA enema preparations. [38,39] A new MMx formulation of mesalamine (SPD476; MMX mesalamine) [40,41] is now undergoing clinical trials.…”
Section: Chemoprevention: the Role Of 5-asa?mentioning
confidence: 99%
“…There was no difference in side effects and patients preferred twice-daily dosing. [36] A study by Lamet and colleagues [37] of 99 patients with ulcerative proctitis found that once-daily dosing of a 1-g extended-release mesalamine suppository was equivalent to a 500-mg twice-daily suppository for the induction of remission, with similar side effects. Finally, a 2-g gel formulation of rectal mesalamine provided similar efficacy to standard mesalamine foam enema for induction of remission at 4 weeks in mild-to-moderate left-sided ulcerative colitis with clinical, endoscopic, and histologic remission rates of 75%, 52%, and 30%, respectively.…”
Section: Chemoprevention: the Role Of 5-asa?mentioning
confidence: 99%
“…Mesalamine suppositories or enemas may be effective in inducing remission for patients unresponsive to oral 5-ASAs or topical steroids particularly for patients with proctitis and distal symptoms 59. Mesalamine suppositories can be dosed at 500 mg twice daily or 1 g once daily; doses of 1 g administered nightly are considered optimal 1,60. The high efficacy and low side effect profile of rectal 5-ASA suppositories makes this formulation the treatment of choice for ulcerative proctitis 46.…”
Section: Mild-to-moderate Ucmentioning
confidence: 99%